The nature, functions and management of urban green space in Kuala Lumpur - Mohd Yusof, Mohd Johari; Rakhshandehroo, Mehdi (Locke Science Publishing Company, 2015)
As Malaysia's population continues to grow and becomes more concentrated in urban areas, the important benefits of urban green spaces to the environment, the economy, and the health and well-being of city residents become even more significant in counterbalancing some of the negative effects of the country's urban development. With this concern in mind, the authors designed a social survey for urban planners and landscape architects in Kuala Lumpur to identify and study their views on the nature, roles, and benefits of urban green spaces; the problems associated with protecting urban green spaces in Kuala Lumpur; and the attributes of green spaces they thought were most important when considering how much priority a particular green space should be given for preservation. Kuala Lumpur provides a particularly interesting case study as a rapidly growing city in a developing country with a tropical climate — a context in which there has been relatively little research on urban green space, despite the importance of shade in very hot climates. In addition, Kuala Lumpur has experienced a great loss of green space in recent decades, both on its periphery from urban expansion and around the city center from the drive (fueled by economic growth) to use central land more intensively.